Energy-Efficient Hybrid PID Control with Exponential Trajectories for Smooth Setpoint Transitions: Applications in Robotics and Aeronautics - Jesús Alberto Meda-Campaña; Israel Isaías Lizardo-Parra; Juan Carlos García-Hernández; Jonathan Omega Escobedo-Alva; Luis Alberto Páramo-Carranza; Ricardo Tapia-Herrera (Applied Sciences, 2025)
In this paper, a modification of the classical PID controller scheme for position control is presented. The resulting controller incorporates an exponential trajectory that smoothly guides the system towards the setpoint and a hybrid mechanism to dynamically reset the exponential signal, allowing an adaptive response to discontinuous reference signals. This combination leverages the benefits of exponential trajectories to reduce overshoot and transient oscillations, while the hybrid system ensures robust performance over a wide range of operating scenarios. Among the advantages of the proposed approach, two stand out: (1) significant improvements in energy savings can be achieved in some cases, and (2) closed-loop system performance can be improved even considering poorly tuned PIDs.